2019
DOI: 10.3390/atmos10090497
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes to Mean and Extreme Surface Wind Speeds for North America Based on Regional Climate Model Simulations

Abstract: This study evaluates projected changes to surface wind characteristics for the 2071–2100 period over North America (NA), using four Global Environmental Multiscale regional climate model simulations, driven by two global climate models (GCMs) for two Representative Concentration Pathway scenarios. For the current climate, the model simulates well the climatology of mean sea level pressure (MSLP) and associated wind direction over NA. Future simulations suggest increases in mean wind speed for northern and east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Another effect of climate variability is the change in wind patterns. As climate changes, so do wind patterns at the global and regional scales (Jeon & Sushama, 2019). This phenomenon affects the dispersal of plant pathogens and pathogen vectors over short and long distances and increases the risk of introduction of new races to areas where they were not previously found.…”
Section: Core Ideasmentioning
confidence: 99%
“…Another effect of climate variability is the change in wind patterns. As climate changes, so do wind patterns at the global and regional scales (Jeon & Sushama, 2019). This phenomenon affects the dispersal of plant pathogens and pathogen vectors over short and long distances and increases the risk of introduction of new races to areas where they were not previously found.…”
Section: Core Ideasmentioning
confidence: 99%
“…Changes in soil temperatures were assumed to be 1°C lower than the projected changes in air temperature based on the work of Zhang et al 61 and Wisser et al 62 . Winter wind speeds were kept constant for all RCPs as predictions by Jeong and Sushama 63 and McInnes et al 64 showed little to no increase in winds speeds in the Ottawa region, in contrast to the predicted increases in regions at higher latitudes in Canada.…”
Section: Climate Projectionsmentioning
confidence: 99%
“…Sutherland et al., 2017). Furthermore, understanding how wind, and changes in wind patterns, affects biodiversity is increasingly relevant as, over the last decade, mean wind speeds have accelerated globally, with the largest changes happening in the Southern Ocean (Young & Ribal, 2019; Zeng et al., 2019), and current predictions suggesting that this trend will continue in the long term (Jeong & Sushama, 2019; Zeng et al., 2019). Therefore, in this study, the impact of wind on fine‐scale vegetation characteristics was assessed by examining the relationship between wind stress (i.e.…”
Section: Introductionmentioning
confidence: 99%